2018
DOI: 10.3390/diagnostics8030055
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Study of Contrast-Enhanced Ultrasound (CEUS) and Cytokine Expression Analysis (CEA) as Early Predictors for the Outcome of Tibial Non-Union Therapy

Abstract: The current study investigates if contrast-enhanced ultrasound (CEUS) or cytokine expression analysis (CEA) evaluating vascularization are capable of predicting the outcome of non-union therapy. Patients with tibial non-unions were surgically treated and participated in our follow-up program including perioperative collection of blood as well as CEUS analysis. Two groups were formed: Responders in group 1 (G1, N = 8) and Non-Responders in group 2 (G2, N = 5). Serum cytokine expression and local microperfusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…Krammer et al reported that early evaluation (examination at 12 week) of successful recovery after tibial non‐union can be realized with CEUS. A study by Haubruck et al reported that a combination of CEUS and peripheral cytokine expression analysis is a promising novel tool in early prediction of the outcome of nonunion therapy. As an improved Doppler technology, SMI technology can display the blood flow in microvessels.…”
Section: Discussionmentioning
confidence: 99%
“…Krammer et al reported that early evaluation (examination at 12 week) of successful recovery after tibial non‐union can be realized with CEUS. A study by Haubruck et al reported that a combination of CEUS and peripheral cytokine expression analysis is a promising novel tool in early prediction of the outcome of nonunion therapy. As an improved Doppler technology, SMI technology can display the blood flow in microvessels.…”
Section: Discussionmentioning
confidence: 99%
“…1,30 A ultrassonografia com contraste (USC) pode fornecer uma indicação precoce de neovascularização e uma base diagnóstica para a regeneração óssea deficiente. 31 A ultrassonografia também pode predizer a formação de calo ósseo ao revelar mudanças no fluxo sanguíneo ao redor do osso novo, o que pode compensar a má visualização precoce do calo na radiografia. 32 A ultrassonografia é um método não invasivo, eficaz, barato e livre de radiação ionizante para avaliar a cicatrização óssea, que pode detectar formação óssea nova quatro a seis semanas antes da radiografia, 26 além de indicar a taxa de formação de osso novo nos estágios iniciais de distração.…”
Section: Valores De Pixels Em Radiologia Digitalunclassified
“…However, new bone with incomplete remodeling and calcification can be well evaluated by high-resolution linear ultrasound [ 35 ]. Contrast-enhanced ultrasound (CEUS) can provide an early indication of neovascularization and provide a diagnostic basis for poor bone regeneration [ 36 ]. Ultrasound can also predict bone callus formation by observing changes in blood flow around the new bone [ 37 ], which can compensate for the poor early visualization of the callus on X-ray.…”
Section: Introductionmentioning
confidence: 99%
“…CEUS can show the microperfusion of local tissue at the capillary level. Through the study of patients with tibial nonunion, Haubruck et al [ 36 ] found a relationship between the expression of different angiogenic cytokines in serum and the change in local microperfusion. They believe that the combined detection of CEUS and cytokine expression analysis (CEA) is a promising new tool for the early prediction of tibial nonunion.…”
Section: Introductionmentioning
confidence: 99%